Mock Paging and Consult Curriculum to Prepare Fourth-Year Medical Students for Medical Internship - Jessica Tischendorf; Clare O'Connor; Madelyn Alvarez; Sara Johnson (Association of American Medical Colleges, 2018)
Introduction Internship preparation should include curricula to hone key skills such as acute medical management and communication with consulting and interprofessional providers. Methods To enhance these skills, we developed an interprofessional mock paging and consult curriculum incorporating direct observation and peer, faculty, and nursing feedback for fourth-year medical students entering medical internships. Our brief mock paging and consult curriculum was designed as part of a larger 2-week internship preparation course. Our curriculum was delivered in two 2-hour sessions by physician and nurse educators. Sessions were conducted in small groups, offering the opportunity for direct observation and feedback from faculty, nurse educators, and peers. Our curriculum was expanded from a pilot for 10-15 students to 60 students after 2 years of a successful pilot. Results Mock paging and consult sessions were highly rated by medical students and resulted in significantly enhanced self-assessment of preparedness in key intern skills such as returning pages, interprofessional communication, calling a consult, and managing acute issues for cross-cover patients. Discussion We have demonstrated the effectiveness of a brief, interprofessional mock paging and consult curriculum incorporating faculty, nurse educator, and peer feedback. The tenets of our curriculum can be widely adopted for other learner groups.